γδ T cells as a potential therapeutic agent for glioblastoma - Kang, In; Kim, Yumin; Lee, Heung Kyu (Frontiers in Immunology, 2023)
Although γδ T cells comprise a small population of T cells, they perform important roles in protecting against infection and suppressing tumors. With their distinct tissue-localizing properties, combined with their various target recognition mechanisms, γδ T cells have the potential to become an effective solution for tumors that do not respond to current therapeutic procedures. One such tumor, glioblastoma (GBM), is a malignant brain tumor with the highest World Health Organization grade and therefore the worst prognosis. The immune-suppressive tumor microenvironment (TME) and immune-evasive glioma stem cells are major factors in GBM immunotherapy failure. Currently, encouraged by the strong anti-tumoral function of γδ T cells revealed at the preclinical and clinical levels, several research groups have shown progression of γδ T cell–based GBM treatment. However, several limitations still exist that block effective GBM treatment using γδ T cells. Therefore, understanding the distinct roles of γδ T cells in anti-tumor immune responses and the suppression mechanism of the GBM TME are critical for successful γδ T cell–mediated GBM therapy. In this review, we summarize the effector functions of γδ T cells in tumor immunity and discuss current advances and limitations of γδ T cell–based GBM immunotherapy. Additionally, we suggest future directions to overcome the limitations of γδ T cell–based GBM immunotherapy to achieve successful treatment of GBM.